PNU-74654 Enhanced the Antiproliferative Activity of Gemcitabine by Targeting Wnt/β-Catenin Pathway in Pancreatic Cancer - Sharifi, Sajjad; Mehrabadi, Shima; Rahmani, Farzad; Nosrati-Tirkani, Abolfazl; Khorrami, Shadi; Khazaei, Majid; Hassanian, Seyed Mahdi; Rajabian, Majid; Boromand, Nadia; Parizade, Seyed Mohammad Reza; Ferns, Gordon A.; Avan, Amir (Clinical Cancer Drugs, 2024)
BackgroundThe Wnt/beta-catenin pathway is one of the pathways that is deregulated in pancreatic cancer and is reported to be associated with a poor prognosis. This indicates the need for the identification of novel agents to improve the efficacy of current therapy or have an improved efficacy. Therefore, in the present study, we explored the anticancer activity of PNU-74654 alone or in combination with gemcitabine in 2 and 3-dimensional cell culture models of pancreatic cancer.MethodsThe MTT assay was carried out to determine the viability of PC cancerous cells (PCCs), while the cytotoxicity of this agent was evaluated in a 3D cell culture model (spheroid). The effects of PNU-74654 were investigated in established cell migration/invasion assays.ResultsThe expression of candidate genes affecting the cell cycle, migration, and Wnt/b-catenin pathway was evaluated at mRNA and/or proteins by RT-PCR or Western blot. PNU-74654 inhibited the cell growth at IC50 of 122 ± 0.4 umol/L and had a synergistic effect on the antiproliferative properties of gemcitabine by modulating the Wnt pathway. The PNU-74654/gemcitabine combination reduced the migratory and invasiveness of PC cells, compared to control cells, through perturbation of E-cadherin.ConclusionOur findings demonstrate the profound antitumor properties of PNU-74654 in in vitro models of pancreatic cancer, supporting further in vivo studies to evaluate the therapeutic impact of this novel therapy to target the Wnt pathway in the treatment of pancreatic cancer.
Keywords: Wnt pathway